THE INFLUENCE OF PROFITABILITY, LEVERAGE, AND GOOD CORPORATE GOVERNANCE ON THE VALUE OF COMPANIES MANUFACTURING THE CONSUMPTION GOODS INDUSTRIAL SECTOR OF THE CIGARETTE SUB-SECTOR LISTED ON THE INDONESIAN STOCK EXCHANGE FOR THE 2017-2021 PERIOD. - Murti, Bayu; Firdaus, Muhammad; Supeni, Nely (MBA : Journal of Management and Business Aplication, 2024)
This study aims to determine the influence of each independent variable used which is profitability, leverage, and good corporate governance on company value. The type of research is quantitative research. The data used is secondary data with collection techniques, literature studies and documentation. The data analysis methods used are classical assumption test, multiple linear regression, coefficient of determination, and hypothesis test. The results of the study show that profitability doesn’t have a partial effect on the value of the company. Leverage has no partial effect on a company’s value. Meanwhile, good corporate governance has a partial and negative effect on company value.